2010
DOI: 10.1021/bi100841u
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Induced Aggregation of Human Monoclonal IgG1 and IgG2: Molecular Mechanism and the Effect of Solution Composition

Abstract: The prevention of aggregation in therapeutic antibodies is of great importance to the biopharmaceutical industry. In our investigation, acid-induced aggregation of monoclonal IgG1 and IgG2 antibodies was studied at pH 3.5 as a function of salt concentration and buffer type. The extent of aggregation was estimated using a native cation-exchange chromatography (CEX) method based on the loss of soluble monomer. This approach allowed quantitative analysis of antibody aggregation kinetics for individual and mixed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 50 publications
12
111
2
Order By: Relevance
“…In brief, the bacterial cells were grown in Mu-eller-Hinton broth to mid-log phase, harvested, and resuspended in buffer as described elsewhere (38). Immediately before the assay was performed, the MAbs were centrifuged for 2 h at 100,000 rpm to remove possible aggregates, since the aggregation of antibodies that occurs during development and storage may lead to the loss of biological activity (39). The 40-l bactericidal reaction mixture contained 1 to 100 g of MAb/ml, ca.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the bacterial cells were grown in Mu-eller-Hinton broth to mid-log phase, harvested, and resuspended in buffer as described elsewhere (38). Immediately before the assay was performed, the MAbs were centrifuged for 2 h at 100,000 rpm to remove possible aggregates, since the aggregation of antibodies that occurs during development and storage may lead to the loss of biological activity (39). The 40-l bactericidal reaction mixture contained 1 to 100 g of MAb/ml, ca.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to effector functions and stability and biophysical characteristics, analytical and regulatory aspects are important selection criteria for such monoclonal antibodies (mAbs) destined for clinical use. Further, it is well known that during manufacturing, purification, formulation, and storage, the isotypes behave differently in terms of their sensitivity to pH or temperature, aggregation propensity, and susceptibility to degradation (11)(12)(13). With regard to monitoring or predicting stability, thermal stability is increasingly accepted as a convenient surrogate measure of global stability.…”
mentioning
confidence: 99%
“…To accelerate bevacizumab aggregation, the incubation temperature was increased. It has previously been shown that when bevacizumab at concentrations below 2.5 mg/mL (pH 6.0-6.2) is incubated at 56 C, 65 C and 70 C, almost all of the protein aggregates within 3 days, 3 h and 10 min, respectively. 21,44 To minimize unfolding of bevacizumab at such a high temperature (temperature close to Tm), a lower temperature was used for these accelerated studies.…”
Section: Mutation Of High Sap Residues Increases Bevacizumab Stabilitymentioning
confidence: 99%